LQG control over a Markov communication network - Nilsson, J.; Bernhardsson, B. (Proceedings of the 36th IEEE Conference on Decision and Control, 1997)
We formulate and solve a control problem where data are sent over a communication network that introduces random time delays. Past time delays are assumed known by the use of time stamps and the probability distribution of future delays are modeled with a Markov chain with continuous observation densities. We generalize previous results on LQG control of jump linear systems to cover this situation.